2020
DOI: 10.1111/joa.13186
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of human arachnoid trabeculae

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
2
9
1
Order By: Relevance
“…To our knowledge, human PAC biomechanical properties have not been documented, and therefore a direct comparison with our results is not possible. While studies using human tissues are limited, the volume fraction in post-mortem human SAT was found to be 5 to 10% greater in frontal regions of the brain compared to other regions [27]. In principle, these differences in volume fraction could lead to relatively small regional differences in mechanical properties, but these relatively small regional differences were not possible to confirm in the present study.…”
Section: Comparison Of Biomechanical Results To Previous Studiescontrasting
confidence: 65%
See 1 more Smart Citation
“…To our knowledge, human PAC biomechanical properties have not been documented, and therefore a direct comparison with our results is not possible. While studies using human tissues are limited, the volume fraction in post-mortem human SAT was found to be 5 to 10% greater in frontal regions of the brain compared to other regions [27]. In principle, these differences in volume fraction could lead to relatively small regional differences in mechanical properties, but these relatively small regional differences were not possible to confirm in the present study.…”
Section: Comparison Of Biomechanical Results To Previous Studiescontrasting
confidence: 65%
“…Scanning electron microscopy and transmission electron microscopy showed that the structural morphology of human (post-mortem) SAT consisted of pillars, columns, sheets, branched fibrils, and other complex structures with fibril diameters that varied from 0.5-3 µm [3]. Optical coherence tomography was utilized to show that SAT fiber diameter varies from 19.2-45.5 µm [27]. Fiber diameter in the human (post-mortem) bulbar subarachnoid space was also found to be between 0.2-1 µm [39].…”
Section: Structural Morphologymentioning
confidence: 99%
“…45 Analysis of postmortem human subjects identified a mean volume fraction of arachnoid trabeculae of ≈25%. 46 The random fibril organisation within the trabeculae is thought to allow for stress redistribution under supraphysiological loading. 45 The arachnoid trabeculae are the main load bearing component of the PAC in normal traction loading but are thought to function primarily in resisting tensile stress, as they buckle under small magnitudes of compressive load.…”
Section: Pia-arachnoid Complex (Pac) Structural Composition and Alignmentmentioning
confidence: 99%
“…SAT consisted of pillars, columns, sheets, branched fibrils, and other complex structures with fibril diameters that varied from 0.5-3 µm [3]. Optical coherence tomography was utilized to show that SAT fiber diameter varies from 19.2-45.5 µm [27]. Fiber diameter in the human (post-mortem)…”
Section: Structural Morphologymentioning
confidence: 99%